Improvement of Antioxidant Activity and Sensory Quality of Pagilaran’s Tea Clones Treated by Tannase - Tri Wahyuni Apriyani; Supriyadi Supriyadi; Rachmad Gunadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2022)
PT. Pagilaran developed five new clones named PGL 9, PGL 10, PGL 11, PGL 12, and PGL 15 for black tea. These clones can be potentially made into ready-to-drink (RTD) instant tea beverages with low antioxidant activity. Tannase is an industrial enzyme with great potential for application in the food industry used to hydrolyze gallated ester catechin in green tea. There were no findings on the effects of this enzyme treatment on the chemical composition of PT Pagilaran’s tea clones. Therefore, this study is aimed to observe the effects of tannase treatment on five clones of black tea extracts to the antioxidant activity, profile of phenolic compounds, the tea brew color, consumer acceptance, and volatile compounds. The leaves of the plucking medium were traditionally processed into black tea. Furthermore, the tea brew was added at a 100 mg/100 mL concentration and then incubated for 1 hour at 37 °C. Additional tannase increased their antioxidant activities, the gallic acid, EC, and EGC concentrations due to hydrolysis of ECG, EGCG, or their derivatives. The color of the tea brew was brighter and yellower than the untreated, but the level of consumer acceptance was still good. The profile aroma and volatile compounds showed no significant changes after enzymatic treatment.